Republic of Equatorial Guinea : 2012 Article IV Consultation: Staff Report, Informational Annex, Public Information Notice, Statement by the Executive Director, Observations by the Government. (IMF Staff Country Reports; Country Report ;, 2013)
This 2012 Article IV Consultation highlights Equatorial Guinea's economic developments and policies. The IMF report focuses on setting priorities that include strengthening fiscal institutions, developing public services, and enhancing governance to push the economic growth. The hydrocarbon sector has continued to be the main driver of the economy, accounting for about three-quarters of estimated GDP. It suggests that a commitment to regular publication and international quality standards would stimulate long-delayed improvements. The prospect of falling hydrocarbon revenues adds urgency to the case for a medium-term fiscal framework.